APLIKASI PANDUAN PENDIDIKAN GROUNDSTAFF PENERBANGANPADA LEMBAGA PENDIDIKAN STAFF PENERBANGAN& PRAMUGARI (PSPP) BERBASIS ANDROID - Nugraha, I Ketut Destian; Wahyuni, Tri (Prosiding Seminar Nasional Darmajaya, 2017)
Groundstaff has basic subjects that must be understood by a prospective groundstaff worker at the airport. It is because (1) the limitations of the subject book, (2) the difficulty of understanding English-book content, (3) the difficulty of understanding withoutÂ  lecturers, and (4) a few of meeting and time on groundstaff.